Research on Classification Criteria for the Reducibility and Irreducibility of Intertrochanteric Femoral Fractures - Fenghua Zhu; Jinya Qiu; Liang Han; Hongxing Xu; Longtao Xiao; Qiushun Zhang; Yifeng Zhao (Orthopaedic Surgery)
ABSTRACT Objective The current classification of intertrochanteric femoral fractures primarily follows the AO/OTA system, which guides treatment but fails to accurately predict preoperative reduction difficulty. Since reduction quality directly impacts fracture healing, internal fixation success, and patient rehabilitation, developing a classification standard that aids in predicting reduction difficulty holds significant clinical implications for achieving optimal outcomes. The purpose of this study was to develop classification criteria for femoral intertrochanteric fractures based on their reducibility and irreducibility and to provide a reference standard for preoperative predictions of the level of difficulty likely to accompany the fracture. Methods Four hundred thirty‐seven patients with intertrochanteric fractures of the femur treated at the Affiliated Hospital of Jining Medical University and several county hospitals from January 2015 to August 2023 were reviewed. The fractures were divided into irreducible and reducible types according to actual intraoperative reduction. The imaging data were collated and analyzed, the type of fracture that may have affected the reduction was selected, the data were collated according to the type of fracture as well as the AO type, unconditional univariate logistic regression analysis was performed, and the OR values were calculated. Results Logistic regression revealed that the risk factors leading to irreducibility were 31A3, 31A3.3, 31A1 (with obvious separation displacement), 31A2 (with anterior angular exostosis) and 31A2 (with a concomitant proximal femur fracture) fractures. Intertrochanteric fractures were typed according to the risk factors suggested by the statistical results and the specific intraoperative imaging manifestations, with irreducibility divided into 3 types and reducibility divided into 2 types, each with their respective subtypes. The accuracy of this typing in predicting the degree of difficulty of intraoperative restoration was 78.4% (343/437), and the test of consistency showed kappa = 0.573 (moderate consistency). Conclusion Classifying intertrochanteric fractures into reducible and irreducible types can accurately preoperatively predict the difficulty of reduction for the vast majority of reducible fractures and most irreducible fractures, guide treatment, and predict the prognosis of the fracture.